Corynebacterium ulcerans pneumonia treated with venovenous extracorporeal membrane oxygenation: a case report. (January 2023) - Takahashi, Yoshihiko; Utsumi, Shu; Sugiura, Gaku; Fujizuka, Kenji; Suzuki, Hiroyuki; Nakamura, Mitsunobu
Highlights: Reports of Corynebacterium ulcerans infection from companion animals are increasing. In pneumonia with pseudomembrane, C. ulcerans pneumonia should be suspected. Venovenous extracorporeal membrane oxygenation is necessary for airway obstruction due to C. ulcerans pneumonia. Abstract: We report the first case of airway obstruction due to toxin-producing Corynebacterium ulcerans, successfully managed with venovenous extracorporeal membrane oxygenation (V-V ECMO). A woman aged 73 years who was living with companion animals was intubated for pneumonia of unknown origin and treated with an empirical antimicrobial agent. Corynebacterium species were detected in the sputum and treated as commensal bacteria. Subsequently, the patient suddenly could not ventilate because of central airway obstruction caused by pseudomembrane formation. Therefore, V-V ECMO was initiated. Additional mass spectrometry identified the Corynebacterium species as C. ulcerans . After treatment with antitoxin, the patient was successfully weaned from V-V ECMO. Hence, in patients in contact with companion animals who present with respiratory failure and pseudomembrane formation, C. ulcerans pneumonia should be suspected and treated with antitoxin. C. ulcerans pneumonia may result in an inability to ventilate due to pseudomembrane formation. Therefore, treatment strategies including V-V ECMO should be considered in such cases.